Vêtements sacerdotaux russes, brodés d’or au monastère d’Iviron du Mont Athos : source de savoir et de mémoire - Nikolaos Mertzimekis (Cahiers balkaniques, 2021)
Abstract: The current assignment discusses the relationships of the monasteries of Mount Athos with Russia, based on two gold‑embroidered vestments, which are kept in sacristies of Athonite monastery Iviron. The ecclesiastical embroidered vestment is kept in the sacristy of the Iviron’s monastery and it is a pair of cuffs (epimanikia), gifts from devoted Christians from Bolsheretskiy ostrog of Kamchatka peninsula.